Effects of Edaravone on Singlet Oxygen Released From Activated Human Neutrophils - Piyanart Sommani; Toshiyuki Arai; Kouhei Yamashita; Takashi Miyoshi; Hiroko Mori; Masataka Sasada; Keisuke Makino (Elsevier, 2007)
The effects of edaravone, a curative agent for acute brain infarction, on singlet oxygen (1O2) released from activated human neutrophils were examined, and the effects were compared to those of histidine, a 1O2 singlet oxygen scavenger. The neutrophils, stimulated with opsonized zymosan, released 1O2 that was detected by chemiluminescence using a 1O2 specific probe, trans-1-(2'-methoxyvinyl)pyrene. Edaravone dose-dependently suppressed the 1O2 release with an IC50 of approximately 0.3 µM, while the IC50 of histidine was approximately 1 mM. This 1O2 scavenging activity of edaravone might be involved in its curative effects on acute brain infarction. Keywords:: edaravone, singlet oxygen, neutrophil